Effect of exercise intensity on active and passive glucose absorption - Lang, J. A.; Gisolfi, C. V.; Lambert, G. P. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
The purpose of this study was to determine the effects of exercise intensity on active and passive intestinal glucose absorption. Eight trained runners (age = 23 ± 2 y; VO2max = 62.1 ± 5.8 mL · kg-1 · min-1) performed a 1 h resting experiment and three 1 h treadmill experiments at 30, 50, or 70% VO2max in a thermoneutral environment. Immediately prior to each experiment, euhydrated subjects ingested a solution containing two non-metabolizable glucose analogs, 3-O-methyl-D-glucose (3MG; actively absorbed; 5 g) and D-xylose (passively absorbed; 5 g). During the following 5 h, all urine was collected and the amount of 3MG and D-xylose in the urine was determined. Using repeated measures ANOVA, a significant (P < 0.05) reduction in urinary excretion of each carbohydrate was observed at 70% VO2max compared to the other intensities suggesting that both active and passive intestinal absorption of glucose may be reduced during prolonged running at this intensity.